Teaching Religious Education : Challenges, Developments and Current Debates in Comparative Perspective - Lucenti, Maria, (Brill Research Perspectives in Humanities and Social Sciences, 2025)
Historically, religious education has often been seen as a tool for reinforcing cultural and religious identity. However, as the world becomes more interconnected and religious diversity grows within national borders, RE has increasingly been called upon to play a different role-one that fosters understanding and peaceful coexistence among people of different faiths and worldviews. The volume Teaching Religious Education: Challenges, Developments, and Current Debates in Comparative Perspective delves into these complexities, offering a comprehensive exploration of how religious education is taught, debated, and implemented across a diverse range of countries, challenging the Eurocentric focus of much existing research on religious education.